Preparation method of carbon material, prepared carbon material and application
By using ether-rich carbon composite materials in lead-carbon batteries to form C-O-Pb bonds, the side reactions of sulfation and hydrogen evolution of the battery in a high-speed partial charging state are solved, which significantly extends the cycle life of the battery and reduces the consumption of electrolyte.
Patent Information
- Application Number
- CN202311155436.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
Lead-carbon batteries are prone to negative electrode sulfation and battery failure in the high-speed partial charging state. The addition of carbon materials leads to side reactions in hydrogen evolution, limiting the performance of the battery.
A low-hydrogen-extraction carbon composite material rich in ether bonds is used to improve the crystallization process and hydrogen evolution overpotential through the C-O bond formed by carbon elements at both ends of the ether bonds.
It effectively improves the crystallization process of lead sulfate, refines the lead sulfate crystal grains, extends the battery cycle life, reduces the precipitation of hydrogen, and reduces the consumption of electrolyte.
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a carbon material, the prepared carbon material and its application, and belongs to the field of conductive materials. Background Art
[0002] Lead-acid batteries have unique characteristics such as low cost and high safety, and their application in hybrid electric vehicles (HEVs) has attracted much attention. However, HEVs require lead-acid batteries to operate under high-rate partial state of charge (HRPSoC), which can lead to negative electrode sulfation and battery failure. Lead-carbon batteries (LCBs) with appropriate carbon added to the negative electrode have the ability to inhibit sulfation and extend the cycle life under HRPSoC. However, the addition of carbon materials brings the hydrogen evolution side reaction problem (HER) to the negative electrode of lead-carbon batteries and limits the performance of LCBs. The hydrogen evolution problem of carbon materials will cause the electrolyte to lose water, reduce the battery energy efficiency, and the generated gas will force the carbon to separate from the sponge lead, thereby destroying the conductive network of the lead-carbon electrode. Summary of the invention
[0003] In order to further solve the sulfation problem of the negative electrode at the end of the lead-carbon battery cycle, solve the problem of too low hydrogen evolution overpotential of carbon materials, and improve the hydrogen evolution overpotential of carbon materials, the present invention proposes a low hydrogen evolution carbon composite material rich in ether bonds, using the CO bonds formed by the two ends of the ether bonds with the carbon element and the O-Pb bonds formed with the lead element to take the lead atom as the crystallization site, and the ether bond itself also has the ability to improve the binding energy of lead ions and sulfate groups, which can effectively improve the lead sulfate crystallization process, refine the lead sulfate grains, and extend the battery cycle life. In addition, a large number of CO-Pb bonds can effectively occupy the hydrogen evolution active sites of carbon materials, improve the hydrogen evolution overpotential of carbon materials, reduce the amount of hydrogen precipitation during the use of lead-carbon batteries, reduce the consumption of battery electrolytes, and further improve the cycle life of lead-carbon batteries.
[0004] According to one aspect of the present application, a method for preparing a carbon material is provided, comprising the following steps:
[0005] Raw materials containing polyethylene oxide, a lead source and water are mixed, reacted in a sealed container, and dried to obtain the carbon material.
[0006] The molecular weight of the polyethylene oxide is 50,000 to 500,000;
[0007] The lead source is selected from at least one of lead nitrate, lead chloride, lead sulfite, lead sulfate, and tetraethyl lead;
[0008] The mass ratio of the polyethylene oxide to the lead source is 100 to 0.01:1;
[0009] The usage ratio of the polyethylene oxide to the water is 0.5-50g:10-10000ml.
[0010] The reaction pressure is 2-20 MPa;
[0011] The reaction temperature is 120-300°C;
[0012] The reaction time is 1 to 48 hours.
[0013] The reaction is carried out in a high pressure hydrothermal autoclave.
[0014] After the reaction, the product was washed with water several times and collected by centrifugation.
[0015] The drying temperature is 60-150°C;
[0016] The drying time is 0.5 to 24 hours.
[0017] According to another aspect of the present application, a carbon material prepared by the preparation method described above is provided, wherein the specific surface area of the carbon material is 50 to 3000 m 2 / g.
[0018] The carbon material contains ether bonds, CO bonds and C-Pb bonds;
[0019] In the carbon material, the mass content of the Pb element is 1 to 40 wt%, and the mass content of the O element is 1 to 40 wt%.
[0020] According to another aspect of the present application, an electrode is provided, comprising the carbon material prepared by the above-mentioned preparation method.
[0021] According to another aspect of the present application, a lead-acid battery is provided, comprising the above-mentioned electrode.
[0022] The beneficial effects of this application include:
[0023] By using the CO bonds formed by the two ends of the ether bond with the carbon element and the O-Pb bonds formed with the lead element, the lead atom is used as the crystallization site to effectively improve the lead sulfate crystallization process, refine the lead sulfate grains, and extend the battery cycle life. In addition, a large number of CO-Pb bonds can effectively occupy the hydrogen evolution active sites of the carbon material, increase the hydrogen evolution overpotential of the carbon material, reduce the amount of hydrogen released during the use of the lead-carbon battery, reduce the consumption of the battery electrolyte, and further increase the cycle life of the lead-carbon battery. DETAILED DESCRIPTION
[0024] Unless otherwise specified, the raw materials in the examples were purchased from commercial sources and used directly without further treatment; the instruments and equipment used were based on the parameters recommended by the manufacturer.
[0025] In the embodiment, the cycle life of the lead-carbon battery is tested using a Blue Electric charge and discharge tester and a Newway charge and discharge tester.
[0026] In the embodiments, the presence of ether bonds -O-, CO bonds and C-Pb bonds in the carbon material and the mass proportion of atoms of each element in the tested sample are obtained by infrared testing (FT-IR) and X-ray photoelectron spectroscopy (XPS) testing, respectively.
[0027] Example 1
[0028] Step 1: Prepare the composite carbon material by the following method:
[0029] 20g of polyethylene oxide with a molecular weight of 100,000 and 20g of lead nitrate were dispersed in 500ml of ultrapure water, and the dispersed solution was transferred to a high-pressure hydrothermal autoclave. The pressure in the hydrothermal autoclave was controlled at about 5MPa and kept at 180 degrees Celsius for 24 hours. The obtained product was washed with ultrapure water for multiple times and centrifuged to collect the product. The product was transferred to an environment of 80 degrees Celsius and dried for 12 hours to obtain an activated carbon material rich in ether bonds. The specific surface area of the prepared activated carbon material was 1200m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 20% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 20% of the total mass of the tested sample.
[0030] Step 2: Prepare lead-carbon battery electrodes and lead-carbon batteries by the following method and conduct cycle stability and gas evolution tests:
[0031] 1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10 minutes to obtain lead paste; (2) Scrape the lead paste onto a metal lead grid with a size of 70mm long, 50mm wide, and 2mm thick, and cure and dry to obtain a lead-carbon battery negative electrode. The curing temperature is 40°C, the humidity is 80%, and the curing time is 20 hours; the drying temperature is 80°C, and the time is 24 hours;
[0032] 2) Preparation of the positive electrode: The positive electrode of the lead-acid battery is prepared according to the same process steps as the negative electrode preparation steps (1) and (2), except that no carbon material is added to the positive electrode;
[0033] 3) Preparation of lead-carbon battery: three positive plates and two negative plates are placed in parallel with each other in an alternating manner, and a colloidal PE separator for lead-carbon battery is placed between the positive plates and the negative plates, and two negative plates are welded in parallel and three positive plates are welded in parallel respectively. The total mass of positive active material of the lead-acid battery (the total mass of the lead paste on the three positive plates after drying) is 60.0g, and the total mass of positive active material refers to the total mass of the lead paste contained in the three positive plates welded in parallel. The total mass of negative active material (the total mass of the lead paste on the two negative plates after drying) is 52.9g, and the total mass of negative active material refers to the total mass of the lead paste contained in the two negative plates welded in parallel. The positive and negative electrode grids are conventional lead grids with dimensions of 70 mm long, 50 mm wide and 2 mm thick. The positive and negative electrodes are placed in a tightly assembled battery box with a length of 76 mm, a width of 40 mm and a height of 100 mm. 83 g of the sulfuric acid electrolyte prepared above with a mass concentration of 1.275 g / ml is injected into the battery box.
[0034] The battery was tested for life at room temperature. The test conditions were: 4.2A constant current discharge for 59 seconds, 18A discharge for 1 second, 6.3A current 2.3V constant current constant voltage charge for 60 seconds at 25°C. The charge and discharge conditions were cycled 3600 times, then left to stand for 40 hours, and then restarted after 40 hours. The termination condition of the life test was that the battery voltage dropped below 1.2V. The assembled internal hybrid battery can run 36804 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the assembled lead-carbon battery can reach 5.1 times the life of traditional lead-acid batteries.
[0035] The battery was subjected to a room temperature gas evolution test, and the test method was as follows: the battery was fully sealed with laboratory-specific commercial paraffin, and then an air duct was inserted into the exhaust port of the battery, the end of the air duct located inside the battery passed through a rubber plug with a length of 5 mm, and the end of the air duct located outside the working electrode chamber was introduced into a device for testing the gas volume by a water displacement method, and the inner and outer surfaces of the rubber plug through which the air duct passed and various connections between the air duct and the commercial water displacement method gas volume test device were firmly sealed with commercial AB glue, in order to ensure that the gas generated by the battery end was completely introduced into the commercial water displacement method gas volume measurement device, and the gas volume generated by the battery end was collected by the device, and the gas production rate was calculated. During the test, the battery system was placed in a constant temperature environment of 25°C, and a constant voltage of 2.4V was applied to both ends of the battery for 48 hours. It was calculated that the gas production rate of the lead-carbon battery of the carbon material of this formula was 0.17ml / (wh·h).
[0036] Example 2
[0037] According to the requirements of Example 1, without changing other conditions, the amount of polyethylene oxide added in step 1 was changed to 10 g. The specific surface area of the activated carbon material prepared by testing was 1300 m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 30% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 10% of the total mass of the tested sample. The assembled internal hybrid battery can run 34079 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.7 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.28ml / (wh·h).
[0038] Example 3
[0039] According to the requirements of Example 1, without changing other conditions, the amount of polyethylene oxide added in step 1 was changed to 50 g. The specific surface area of the activated carbon material prepared by testing was 1800 m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 10% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 40% of the total mass of the tested sample. The assembled internal hybrid battery can run 30430 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.2 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.30ml / (wh·h).
[0040] Example 4
[0041] According to the requirements of Example 1, without changing other conditions, the molecular weight of polyethylene oxide in step 1 was changed to 50,000. The specific surface area of the activated carbon material prepared by testing was 1000m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 10% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 30% of the total mass of the tested sample. The assembled internal hybrid battery can run 25394 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.5 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.18ml / (wh·h).
[0042] Example 5
[0043] According to the requirements of Example 1, without changing other conditions, the molecular weight of polyethylene oxide in step 1 was changed to 500,000. The specific surface area of the activated carbon material prepared by testing was 2000m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 5% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 40% of the total mass of the tested sample. The assembled internal hybrid battery can run 26677 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.7 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.16ml / (wh·h).
[0044] Example 6
[0045] According to the requirements of Example 1, without changing other conditions, the pressure of the hydrothermal reactor in step 1 was changed to 2 MPa. The specific surface area of the prepared activated carbon material was 1400 m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 25% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 15% of the total mass of the tested sample. The assembled internal hybrid battery can run 26856 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.7 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.20ml / (wh·h).
[0046] Example 7
[0047] According to the requirements of Example 1, without changing other conditions, the pressure of the hydrothermal reactor in step 1 was changed to 20 MPa. The specific surface area of the prepared activated carbon material was 500 m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, and the atomic mass of Pb element accounts for 30% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 20% of the total mass of the tested sample. The assembled internal hybrid battery can run 21805 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.0 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.24ml / (wh·h).
[0048] The above embodiments show that as the molecular weight of polyethylene oxide increases, the specific surface area of the product carbon material gradually increases, and as the pressure of the reaction environment increases, the specific surface area of the product carbon material gradually decreases, and the content of ether bond -O-, CO bond and C-Pb bond has a strong relationship with the reaction conditions.
[0049] Comparative Example 1
[0050] Lead-acid battery: According to the requirements of Example 1, without changing other conditions, step 2 "1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" was changed to (without adding any carbon material) "1) Preparation of negative electrode: (1) Premix 600g lead powder, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" without adding other steps, and the lead-acid battery was prepared. The assembled internal hybrid battery can run 7200 cycles in the normal temperature life test. Lead-acid batteries do not have hydrogen evolution problems, so gas generation rate testing is not performed.
[0051] Comparative Example 2
[0052] Lead-carbon battery: According to the requirements of Example 1, other conditions were not changed, and the composite carbon material was not prepared. A lead-carbon battery with a specific surface area of 1300 m 2 / g of commercial activated carbon is used as a carbon material additive for lead-carbon batteries. The assembled internal hybrid battery can run 10,800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.40ml / (wh·h). The test shows that there is no C-Pb bond in the commercial activated carbon, and the -O- bond peak in the spectrum is weak, and the oxygen element accounts for less than 1%. Therefore, the battery gas production rate is relatively high, the hydrogen evolution problem is relatively serious, and the cycle life is not high.
[0053] Comparative Example 3
[0054] According to the requirements of Example 1, without changing other conditions, the amount of polyethylene oxide added in step 1 was changed to 0.5 g. The specific surface area of the activated carbon material prepared by testing was 1100 m 2 / g, the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, but the atomic mass of Pb element accounts for 80% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 0.5% of the total mass of the tested sample. Because the proportion of Pb element in the prepared carbon material is too high and the proportion of -O- bond is too low, a stable CO-Pb bond cannot be formed, and the Pb element cannot effectively inhibit the hydrogen evolution of the carbon material. The assembled internal hybrid battery can run 6285 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.50ml / (wh·h).
[0055] Comparative Example 4
[0056] According to the requirements of Example 1, without changing other conditions, the molecular weight of polyethylene oxide in step 1 was changed to 10,000. Since the molecular weight of polyethylene oxide was too low, the specific surface area of the prepared carbon material was only 20 m 2 / g, resulting in the carbon material being unable to exert its advantages of high conductivity and continued sulfuric acid electrolyte, and the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond after testing, but the atomic mass of the Pb element accounts for 70% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 30% of the total mass of the tested sample. Similar to the reasons in comparative example 3, the prepared carbon material has a serious problem of hydrogen evolution, and the assembled internal hybrid battery can only run 3603 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.59ml / (wh·h).
[0057] Comparative Example 5
[0058] According to the requirements of Example 1, without changing other conditions, the pressure of the hydrothermal autoclave in step 1 was changed to 1 MPa. Since the pressure in the hydrothermal autoclave was too low, the polyethylene oxide precursor could not reach the thermodynamic conditions for conversion into carbon material, and the preparation of carbon material and the assembly of lead-carbon battery could not be completed.
[0059] Comparative Example 6
[0060] According to the requirements of Example 1, without changing other conditions, the pressure of the hydrothermal reactor in step 1 was changed to 30 MPa. Due to the excessive pressure in the hydrothermal reactor, the specific surface area of the prepared carbon material could only reach 5 m 2 / g, and the prepared carbon material contains ether bond -O-, CO bond and C-Pb bond, but the atomic mass of Pb element accounts for 90% of the total mass of the tested sample, and the atomic mass of oxygen element accounts for 5% of the total mass of the tested sample. Similar to the reasons in comparative example 3, the prepared carbon material has a serious hydrogen evolution problem, and the assembled internal hybrid battery can run 7200 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.82ml / (wh·h).
[0061] Comparative Example 7
[0062] According to the requirements of Example 1, without changing other conditions, the polyethylene oxide used in step 1 is replaced with polypropylene oxide of equal mass and similar molecular weight. Since polypropylene oxide cannot form the required carbon material rich in ether bonds in the provided preparation environment, and the prepared carbon material contains only C-Pb bonds after testing, the crystallization process of lead sulfate cannot be effectively regulated. The assembled internal hybrid battery can run 4910 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.46ml / (wh·h).
[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a carbon material, characterized in that: The following steps are involved: Raw materials containing polyethylene oxide, a lead source and water are mixed, reacted in a sealed container, and dried to obtain the carbon material.
2. The preparation method according to claim 1, characterized in that: The molecular weight of the polyethylene oxide is 50,000 to 500,000; The lead source is selected from at least one of lead nitrate, lead chloride, lead sulfite, lead sulfate, and tetraethyl lead; The mass ratio of the polyethylene oxide to the lead source is 100 to 0.01:1; The usage ratio of the polyethylene oxide to the water is 0.5-50g:10-10000ml.
3. The preparation method according to claim 1, characterized in that: The reaction pressure is 2-20 MPa; The reaction temperature is 120-300°C; The reaction time is 1 to 48 hours.
4. The preparation method according to claim 1, characterized in that: The drying temperature is 60-150°C; The drying time is 0.5 to 24 hours.
5. A carbon material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The specific surface area of the carbon material is 50 to 3000 m 2 / g.
6. The carbon material according to claim 5, characterized in that The carbon material contains ether bonds, CO bonds and C-Pb bonds; In the carbon material, the mass content of the Pb element is 1 to 40 wt%, and the mass content of the O element is 1 to 40 wt%.
7. An electrode, characterized in that: A carbon material prepared by the preparation method according to any one of claims 1 to 4.
8. A lead-acid battery, characterized in that: Containing the electrode according to claim 7.